A zinc-air battery gel electrolyte based on hierarchical alkali lignin and a preparation method thereof
Patent Information
- Application Number
- CN202611139647.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-07-30
AI Technical Summary
[0005]针对现有技术存在的不足,本发明的目的是提供一种基于分级碱木素的锌空气电池凝胶电解质及其制备方法,旨在解决现有PVA基凝胶电解质离子电导率偏低、保水性差、机械强度不足的技术问题,同时实现碱木素资源的高值化利用
通过95%乙醇分级处理,从碱木素中分离得到分子量较低、活性官能团更丰富的分级碱木素(组分一)。该分级碱木素富含酚羟基、醇羟基和羧基,在PVA凝胶网络中分散均匀,能与PVA分子链形成密集的氢键交联点,同时这些极性基团可作为额外的离子跳跃位点,构建连续、高效的离子传输通道,可以显著提升凝胶电解质的离子电导率。
Smart Images

Figure CN122659406B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of gel electrolyte technology, specifically relating to a zinc-air battery gel electrolyte based on graded alkali lignin and its preparation method. Background Technology
[0002] The statements herein provide only background information in relation to this invention and do not necessarily constitute prior art.
[0003] Zinc-air batteries possess advantages such as high theoretical energy density, good safety, and low cost, and are considered to be highly promising next-generation electrochemical energy storage devices. However, the liquid alkaline electrolyte used in traditional zinc-air batteries suffers from problems such as easy leakage, zinc dendrite growth, and carbonation, which severely restrict their cycle stability and practical applications.
[0004] Gel electrolytes, as quasi-solid-state electrolytes, effectively suppress electrolyte leakage and possess a certain mechanical strength, hindering the penetration of zinc dendrites, thus attracting widespread attention. Polyvinyl alcohol (PVA)-based hydrogels, due to their excellent film-forming properties, chemical stability, and biocompatibility, have become a commonly used matrix material for gel electrolytes. In existing technologies, PVA hydrogels are typically prepared using freeze-thaw or chemical cross-linking methods, followed by immersion in an alkaline electrolyte solution to obtain PVA-based gel electrolytes. However, the ionic conductivity and electrochemical stability of PVA gel electrolytes still need improvement. Their poor water retention and limited mechanical strength make it difficult to effectively suppress long-term zinc dendrite penetration. Therefore, how to simultaneously improve the ionic conductivity, water retention, and mechanical properties of PVA gels while maintaining structural stability has become a pressing technical challenge in this field. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the present invention aims to provide a zinc-air battery gel electrolyte based on graded alkali lignin and its preparation method, thereby solving the technical problems of low ionic conductivity, poor water retention, and insufficient mechanical strength of existing PVA-based gel electrolytes, while realizing the high-value utilization of alkali lignin resources.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solution: In a first aspect, the present invention provides a method for preparing a zinc-air battery gel electrolyte based on graded alkali lignin, comprising the following steps: Alkali lignin is mixed with an aqueous alcohol solution, stirred to dissolve, and the dissolved portion is collected. The solvent in the dissolved portion is removed to obtain graded alkali lignin, wherein the volume fraction of the aqueous alcohol solution is ≥80%. Graded alkali lignin is dissolved in an alkaline electrolyte solution to obtain an alkaline solution containing graded alkali lignin. The solutes in the alkaline electrolyte solution are potassium hydroxide and zinc acetate, with the concentration of potassium hydroxide being 4-7 mol / L and the concentration of zinc acetate being 0.1-0.5 mol / L. After degassing an aqueous solution of polyvinyl alcohol, it is subjected to directional freezing and thawing to obtain a PVA hydrogel with a directional pore structure. The PVA hydrogel was immersed in an alkaline solution containing graded alkali lignin to obtain a gel electrolyte.
[0007] Secondly, the present invention provides a zinc-air battery gel electrolyte based on graded alkali lignin, which is prepared by the aforementioned preparation method.
[0008] The beneficial effects achieved by one or more embodiments of the present invention described above are as follows: Fractionated alkali lignin (component 1) with lower molecular weight and richer active functional groups was isolated from alkali lignin through fractionation with 95% ethanol. This fractionated alkali lignin is rich in phenolic hydroxyl, alcoholic hydroxyl, and carboxyl groups, and is uniformly dispersed in the PVA gel network. It can form dense hydrogen bond crosslinking points with PVA molecular chains. At the same time, these polar groups can serve as additional ion jumping sites, constructing continuous and efficient ion transport channels, which can significantly improve the ionic conductivity of the gel electrolyte.
[0009] The phenolic hydroxyl and carboxyl groups in the hierarchical lignin molecule anchor water molecules through strong hydrogen bonds, forming a stable hydration layer that effectively inhibits moisture evaporation in room temperature air. The hydrophobic three-dimensional framework of lignin further binds free water, synergistically slowing down the drying of the gel electrolyte and effectively improving its water retention and anti-drying ability. This improved water retention ensures a stable ion conduction environment during long-term cycling, extending the battery's working life.
[0010] Hierarchical alkali lignin (component one) forms a dense hydrogen-bonded cross-linked network with PVA molecular chains, which, as a nano-reinforcing phase, can significantly improve the tensile strength and elongation at break of the gel. Simultaneously, its polar functional groups are uniformly adsorbed at the gel / zinc anode interface, promoting uniform zinc ion distribution through electrostatic interactions, reducing local concentration gradients, preventing dendrite growth, and synergistically inhibiting zinc dendrite penetration in conjunction with the physical barrier.
[0011] An anisotropic channel structure with unidirectional growth from bottom to top was constructed in PVA hydrogel by rapid directional freezing of copper blocks with liquid nitrogen assistance combined with subsequent freezing at -20°C. This directional channel structure is beneficial for K... + and OH - Ions are transported rapidly and with low impedance along the freezing direction, reducing concentration polarization.
[0012] Alkali lignin is a byproduct of the papermaking industry, widely available and inexpensive. Using it in gel electrolytes achieves high-value utilization of waste, aligning with green chemistry principles. This invention eliminates the need for complex chemical cross-linking reactions; high-performance gel electrolytes can be obtained through physical freeze-thaw cycles and soaking. The soaking method is simple to operate, using only conventional industrial equipment, facilitating large-scale production and widespread application. Attached Figure Description
[0013] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.
[0014] Figure 1 This is a comparison chart of the ionic conductivity of the gel electrolytes obtained in Examples 1-3 and Comparative Examples 1-4 of the present invention; Figure 2 The stress-strain curves of the gel electrolytes obtained in Examples 1-3 and Comparative Examples 1-4 of this invention are shown. Figure 3 The graph shows the water retention rate of the gel electrolytes obtained in Example 1 and Comparative Examples 1-4 of the present invention as a function of time (48 h) in air at room temperature. Figure 4 The zinc-air batteries assembled in Example 1 and Comparative Examples 1-4 of this invention were used at a current density of 2 mA / cm². 2 The discharge curve; Figure 5 The zinc-air batteries assembled in Example 1 and Comparative Examples 1-4 of this invention were used at a current density of 2 mA / cm². 2 The constant current charge-discharge curve. Detailed Implementation
[0015] It should be noted that the following detailed description is illustrative and intended to provide further explanation of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0016] To address the technical problems mentioned in the background art, the present invention provides a method for preparing a zinc-air battery gel electrolyte based on graded alkali lignin, comprising the following steps: Alkali lignin is mixed with an aqueous alcohol solution, stirred to dissolve, and the dissolved portion is collected. The solvent in the dissolved portion is removed to obtain graded alkali lignin, wherein the volume fraction of the aqueous alcohol solution is ≥80%. Graded alkali lignin is dissolved in an alkaline electrolyte solution to obtain an alkaline solution containing graded alkali lignin. The solutes in the alkaline electrolyte solution are potassium hydroxide and zinc acetate, with the concentration of potassium hydroxide being 4-7 mol / L and the concentration of zinc acetate being 0.1-0.5 mol / L. After degassing an aqueous solution of polyvinyl alcohol, it is subjected to directional freezing and thawing to obtain a PVA hydrogel with a directional pore structure. The PVA hydrogel was immersed in an alkaline solution containing graded alkali lignin to obtain a gel electrolyte.
[0017] Alkali lignin is an abundant and renewable natural polymer containing numerous polar functional groups such as phenolic hydroxyl, alcoholic hydroxyl, and carboxyl groups, exhibiting certain alkali solubility and ion conduction potential. However, unclassified alkali lignin has a wide molecular weight distribution and heterogeneous structure. Low molecular weight components easily precipitate from the gel network, while high molecular weight components are difficult to disperse, leading to severe aggregation in the PVA matrix and hindering its full functionality. Adding small amounts has limited performance improvement, while excessive addition can damage the gel network structure and reduce mechanical strength.
[0018] Impurities at both ends of the molecular weight distribution are removed by fractionation treatment with ethanol (90% or more by volume), resulting in fractionated alkali lignin with concentrated molecular weight and high functional group activity. This fractionated alkali lignin is rich in phenolic hydroxyl, alcoholic hydroxyl, and carboxyl groups, which can form dense hydrogen bond crosslinking points with PVA molecular chains, significantly improving the tensile strength and elongation at break of the gel electrolyte. Simultaneously, these polar groups can serve as additional ion hopping sites, constructing continuous and efficient ion transport channels, effectively enhancing ionic conductivity.
[0019] The phenolic hydroxyl and carboxyl groups in hierarchical lignin molecules can anchor water molecules through strong hydrogen bonds, forming a stable hydration layer that effectively inhibits moisture evaporation in room temperature air. The hydrophobic three-dimensional framework of lignin further binds free water, effectively improving the water retention rate of the gel electrolyte and thus maintaining the ion conduction environment during long-term cycling.
[0020] The abundant polar functional groups (phenolic hydroxyl groups, carboxyl groups, etc.) in graded alkali lignin can promote the uniform distribution of zinc ions on the electrode surface through electrostatic interactions, reduce local concentration differences, and prevent tip growth. At the same time, the enhanced hydrogen bond cross-linking network endows the gel with higher mechanical modulus, forming a physical barrier and synergistically inhibiting the penetration of zinc dendrites.
[0021] Anisotropic channels growing unidirectionally from bottom to top were constructed in PVA hydrogel using liquid nitrogen-assisted rapid directional freezing of a metal block followed by -20°C subsequent freezing. This directional channel structure is beneficial for K... + and OH - Ions are transported rapidly and with low impedance along the freezing direction, reducing concentration polarization, stabilizing the discharge voltage plateau above 1.2 V, and significantly improving rate performance and charge-discharge cycle stability.
[0022] In some embodiments, the alcohol in the aqueous alcohol solution is methanol, ethanol, or isopropanol.
[0023] Preferably, the volume fraction of the alcohol aqueous solution is ≥90%.
[0024] In some embodiments, the solvent removal method for the dissolved portion is rotary evaporation concentration to remove ethanol, followed by freeze drying to fractionate alkali lignin.
[0025] In some embodiments, the solutes in the alkaline electrolyte solution are potassium hydroxide and zinc acetate, wherein the concentration of potassium hydroxide is 4-6 mol / L and the concentration of zinc acetate is 0.1-0.3 mol / L.
[0026] The concentration of potassium hydroxide can be 4 mol / L, 5 mol / L, 6 mol / L or 7 mol / L; The concentration of zinc acetate can be 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, or 0.5 mol / L.
[0027] Potassium hydroxide completely dissociates into K+ in aqueous solution. + and OH - Ions provide a highly conductive medium for ion transport within the battery, ensuring rapid ion migration during charging and discharging, thereby improving the battery's charge / discharge rate and power density. High-concentration KOH solution has high ionic conductivity, effectively reducing battery internal resistance, minimizing energy loss, and improving energy conversion efficiency. Furthermore, potassium hydroxide, as a major component of the electrolyte, directly participates in the battery's electrochemical reactions and is one of the key substances for normal battery operation.
[0028] Zinc acetate dissociates into Zn in aqueous solution. 2+ and CH3COO - Zn ions provide a zinc ion source for the charging and discharging process of the zinc electrode. During charging, Zn... 2+ Ions gain electrons on the zinc electrode surface and are reduced to zinc metal, thus regenerating the zinc electrode; CH3COO in zinc acetate - Ions can react with Zn 2+ Zinc acetate forms stable complexes, altering the form of zinc ions in the electrolyte and reducing their activity. This slows down the deposition rate of zinc ions on the electrode surface and inhibits the growth of zinc dendrites. The formation of these complexes also makes the distribution of zinc ions on the electrode surface more uniform, reducing local concentration gradients and preventing dendrite growth, further inhibiting the formation of zinc dendrites. Zinc acetate can improve the stability of the electrolyte, reduce its volatilization and decomposition, and extend its service life.
[0029] Preferably, in the alkaline electrolyte, the concentration of potassium hydroxide is 5-7 mol / L and the concentration of zinc acetate is 0.1-0.3 mol / L.
[0030] In some embodiments, the alkaline solution containing graded alkali lignin has a mass-volume concentration of 0.1%-0.5%, w / v.
[0031] The mass-volume concentration of graded alkali lignin can be 0.1%, 0.2%, 0.3%, 0.4%, or 0.5%.
[0032] In some embodiments, the concentration of polyvinyl alcohol in the aqueous solution is 5-15%, w / v. Specifically, it can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, or 15%.
[0033] Preferably, the concentration of polyvinyl alcohol is 8-12%, w / v.
[0034] In some embodiments, the method of directional freezing and thawing is as follows: pouring a polyvinyl alcohol solution into a mold, and applying a metal block in contact with liquid nitrogen to one side of the polyvinyl alcohol solution to perform rapid directional freezing; After complete freezing, transfer the mold to an environment of -25~-15℃ and continue freezing for 10-15 hours; Then thaw at 20-30℃.
[0035] The rapid directional freezing stage primarily establishes the initial temperature gradient and ice crystal growth direction. However, due to the rapid cooling rate, ice crystal growth may not be sufficient or uniform. Subsequent freezing in an environment of -25 to -15°C allows the ice crystals to grow and mature further under relatively mild conditions, forming a more uniform and continuous ice crystal network. After thawing and removal, this uniform ice crystal network leaves behind a well-structured, porous structure with a uniform pore size distribution, providing more unobstructed channels for ion transport.
[0036] The rapid directional freezing stage primarily establishes the initial temperature gradient and ice crystal growth direction. However, due to the rapid cooling rate, ice crystal growth may not be sufficient or uniform. Subsequent freezing in an environment of -25 to -15°C allows the ice crystals to grow and mature further under relatively mild conditions, forming a more uniform and continuous ice crystal network. After thawing and removal, this uniform ice crystal network leaves behind a well-structured, porous structure with a uniform pore size distribution, providing more unobstructed channels for ion transport.
[0037] During rapid directional freezing, polymer molecular chains initially align along the freezing direction under the pressure of ice crystals, but this alignment may not be stable or complete. Subsequent cryogenic freezing allows sufficient time for the molecular chains to rearrange and orient, forming a more stable oriented structure. This oriented structure significantly improves the mechanical strength and toughness of the gel electrolyte, giving it better resistance to damage under external forces. The low-temperature environment helps polymer molecular chains form more hydrogen bonds and physical cross-linking points, thereby increasing the cross-linking density of the gel. Higher cross-linking density enhances the stability of the gel's network structure, reduces its swelling rate in body fluid environments, and also improves the gel's water retention and freeze-thaw resistance. Studies have shown that PVA hydrogels prepared by extending the freezing time exhibit significantly increased cross-linking density, as well as markedly improved water retention and freeze-thaw resistance.
[0038] During rapid directional freezing, the fast cooling rate can prevent polymer molecules and additives from distributing evenly in the solution, leading to component segregation. Subsequent low-temperature freezing allows sufficient time for the various components in the solution to diffuse and distribute evenly, reducing segregation and improving the overall homogeneity of the gel. A uniform component distribution helps ensure the consistency and stability of the gel electrolyte's performance. Prolonged low-temperature freezing further stabilizes the gel's network structure, reducing structural changes during subsequent processing and use. A stable network structure ensures that the gel electrolyte maintains good performance under various environmental conditions, extending its service life.
[0039] Appropriate low-temperature treatment can lower the glass transition temperature of gel electrolytes, allowing them to maintain good flexibility and ion transport performance even at low temperatures.
[0040] Preferably, the directional freezing and thawing operation is repeated 2-4 times; during each directional freezing, the metal block acts on the same side of the polyvinyl alcohol.
[0041] In some embodiments, the PVA hydrogel is soaked in the alkaline solution containing graded alkali lignin for 10-15 hours at a soaking temperature of 20-30°C.
[0042] Secondly, the present invention provides a zinc-air battery gel electrolyte based on graded alkali lignin, which is prepared by the aforementioned preparation method.
[0043] The present invention will be further described below with reference to the embodiments.
[0044] Example 1 S1: Take 10 g of alkali lignin (Maclean) and add it to 500 mL of 95% (v / v) ethanol aqueous solution. Stir at room temperature for 30 min to ensure complete dissolution. Filter under vacuum and collect the filtrate (dissolved portion) and filter residue separately. Concentrate the filtrate by rotary evaporation at 40°C, remove the ethanol, and freeze-dry for 48 hours to obtain component one (graded alkali lignin).
[0045] S2: Weigh 0.3 g of component one (graded alkali lignin) and dissolve it in 100 mL of a mixed aqueous solution containing 6 mol / L potassium hydroxide and 0.2 mol / L zinc acetate. Stir at room temperature until completely dissolved to obtain an alkaline solution containing alkali lignin.
[0046] S3: Weigh 10 g of polyvinyl alcohol (average degree of polymerization 1799, degree of alcoholysis 98-99%), add it to 90 mL of deionized water, and stir in a 90°C oil bath for 2 h until completely dissolved to obtain a 10% (w / v) PVA precursor solution. After allowing the PVA solution to stand to remove bubbles, pour it into a polytetrafluoroethylene mold (20 mm × 20 mm × 2 mm) with a copper sheet bottom.
[0047] The mold was placed on the surface of a copper block in contact with liquid nitrogen for rapid directional freezing: it was pre-immersed in liquid nitrogen and cooled to -196°C, then the bottom of the mold was pressed tightly against the upper surface of the copper block, allowing the PVA solution to freeze rapidly in one direction from bottom to top, completely solidifying within approximately 60 seconds. The mold was then quickly transferred to a -20°C freezer for further freezing for 12 hours. It was then removed and thawed at room temperature (approximately 25°C) for 6 hours, completing one freeze-thaw cycle. This process (rapid freezing of the copper block in liquid nitrogen → freezing at -20°C for 12 hours → thawing at room temperature for 6 hours) was repeated three times to obtain a PVA hydrogel with a directional pore structure.
[0048] S4: Remove the PVA hydrogel obtained in S3 from the mold and immerse it completely in the alkaline solution containing alkali lignin prepared in S2. Soak at 25°C for 12 hours. After removal, gently absorb the excess solution on the surface with filter paper to obtain the gel electrolyte.
[0049] Assembly of the zinc-air battery: The zinc sheet (2 cm × 3 cm × 0.2 mm), the prepared gel electrolyte (2 cm × 2 cm × 2 mm), and the air cathode (2 cm × 3 cm × 1 mm) were stacked in a sandwich structure. The battery was sealed with a sealing film to ensure that all components except the air cathode side (exposed to air) were isolated from the ambient atmosphere. All assembly operations were performed in air at room temperature.
[0050] The method for preparing an air cathode is as follows: Weigh 2.5 mg Pt / C and 2.5 mg RuO2, add 980 μL anhydrous ethanol and 20 μL Nafion solution (5wt%), and sonicate for 30 min until a homogeneous catalyst ink is formed. Cut a commercial nickel mesh electrode to a size that matches the gel electrolyte, and uniformly drop 200 μL of catalyst ink onto one side surface of the nickel mesh (approximately 1 cm). 2 Within the region, an air cathode with a catalyst loading of approximately 1.0 mg / cm² was prepared by drying at room temperature.
[0051] Example 2 The method is basically the same as in Example 1, except that 0.1 g of component one is weighed and dissolved in 100 mL of a mixed aqueous solution containing 6 mol / L potassium hydroxide and 0.2 mol / L zinc acetate (mass / volume concentration 0.1%).
[0052] The assembly method for the zinc-air battery is the same as in Example 1.
[0053] Example 3 The process is basically the same as in Example 1, except that 0.5 g of component one is weighed and dissolved in 100 mL of a mixed aqueous solution containing 6 mol / L potassium hydroxide and 0.2 mol / L zinc acetate (mass / volume concentration 0.5%).
[0054] The assembly method for the zinc-air battery is the same as in Example 1.
[0055] Example 4 This is essentially the same as Example 1, except that in S1, the volume fraction of the aqueous ethanol solution used is 90%. Everything else is the same as in Example 1.
[0056] Example 5 This is essentially the same as Example 1, except that in S1, the volume fraction of the aqueous ethanol solution used is 80%. Everything else is the same as in Example 1.
[0057] Example 6 The process is essentially the same as in Example 1, except that in S1, the 95% ethanol aqueous solution is replaced with an 80% methanol solution. Everything else is the same as in Example 1.
[0058] Example 7 The process is essentially the same as in Example 1, except that in S1, the 95% ethanol aqueous solution is replaced with an 80% isopropanol solution. Everything else is the same as in Example 1.
[0059] Comparative Example 1 It is basically the same as Example 1, except that: ungraded alkali lignin (raw alkali lignin that has not been treated with any ethanol) is used instead of component one, and the rest of the steps are the same.
[0060] The assembly method for the zinc-air battery is the same as in Example 1.
[0061] Comparative Example 2 It is basically the same as Example 1, except that component two (graded alkali lignin) is used instead of component one, and the rest of the steps are the same.
[0062] The preparation method of component two is as follows: The filter residue collected in step S1 of Example 1 was added to 500 mL of an 80% (v / v) ethanol aqueous solution and stirred at room temperature for 30 min. After filtration, the filtrate and filter residue were collected separately. The filtrate was dried by rotary evaporation to obtain component two (80% ethanol soluble).
[0063] The assembly method for the zinc-air battery is the same as in Example 1.
[0064] Comparative Example 3 It is basically the same as Example 1, except that component three is used instead of component one, and the rest of the steps are the same.
[0065] Component 3 is obtained by drying the filter residue from Comparative Example 2.
[0066] The assembly method for the zinc-air battery is the same as in Example 1.
[0067] Comparative Example 4 The procedure is essentially the same as in Example 1, except that no alkali lignin is added in S2, and in S4, the PVA hydrogel obtained in S3 is removed from the mold and completely immersed in an alkaline solution containing 6 mol / L KOH and 0.2 mol / L zinc acetate for 12 h at 25°C. After removal, excess solution is gently absorbed from the surface with filter paper to obtain the gel electrolyte.
[0068] The assembly method for the zinc-air battery is the same as in Example 1.
[0069] Comparative Example 5 The process is essentially the same as in Example 1, except that in S1, the 95% (v / v) aqueous ethanol solution is replaced with anhydrous ethanol. All other aspects are identical to Example 1. Anhydrous ethanol has insufficient polarity and hydrogen bonding, making it unable to effectively disrupt the association between lignin molecules. Therefore, lignin has extremely poor solubility in it, making it difficult to obtain lignin fractionation components.
[0070] Comparative Example 6 It is basically the same as Example 1, except that the step of "moving to a -20°C freezer for 12 hours" is omitted. Everything else is the same as Example 1.
[0071] Specifically, the mold was placed on the surface of a copper block in contact with liquid nitrogen for rapid directional freezing: it was pre-immersed in liquid nitrogen and cooled to -196°C, then the bottom of the mold was pressed tightly against the upper surface of the copper block, allowing the PVA solution to freeze rapidly in one direction from bottom to top, completely solidifying within approximately 60 seconds. It was then removed and thawed at room temperature (approximately 25°C) for 6 hours, completing one freeze-thaw cycle. This process was repeated three times (rapid freezing of the copper block in liquid nitrogen → freezing at -20°C for 12 hours → thawing at room temperature for 6 hours) to obtain a PVA hydrogel with a directional pore structure.
[0072] Comparative Example 7 It is basically the same as Example 1, except that the step of directional freezing is omitted. Everything else is the same as Example 1.
[0073] Specifically, the mold was rapidly transferred to a -20°C freezer and frozen for 12 hours. It was then removed and thawed at room temperature (approximately 25°C) for 6 hours, completing one freeze-thaw cycle. This process (rapid freezing of the liquid nitrogen copper block → freezing at -20°C for 12 hours → thawing at room temperature for 6 hours) was repeated three times to obtain a PVA hydrogel with a directional pore structure.
[0074] Comparative Example 8 The process is essentially the same as in Example 1, except that in S1, the 95% (v / v) aqueous ethanol solution is replaced with n-hexane. Because n-hexane lacks sufficient polarity to effectively disrupt the association between lignin molecules, alkali lignin has extremely poor solubility in n-hexane solution, being almost insoluble, thus making it impossible to obtain lignin fractionation components.
[0075] Comparative Example 9 The process is essentially the same as in Example 1, except that in S1, the 95% (v / v) aqueous ethanol solution is replaced with petroleum ether. Because petroleum ether has low polarity and lacks hydrogen bonding, it cannot effectively disrupt the association between lignin molecules, and alkali lignin is almost insoluble, thus making it impossible to obtain lignin fractionation components.
[0076] Performance testing: Relevant test methods for ionic conductivity, water retention, mechanical strength, battery discharge time, and cycle time: Ionic conductivity: The gel electrolyte was sandwiched between two copper plates, and the data was recorded using an electrochemical workstation.
[0077] Water retention: The gel electrolyte (initial mass m) o Place it in an environment of 25℃ and 30% relative humidity, and weigh it at regular intervals (m). t Record the water retention rate after 48 hours.
[0078] Water retention rate calculation: Water retention rate = m t / m o× 100%; Mechanical strength: The tensile strength and elongation at break of the gel were tested using a texture analyzer. In the tensile test, the gel electrolyte was prepared into strips of 5 × 1 × 0.1 cm, cut using a mold, and the sample position was fixed. The tensile speed was set to 120 mm·min. -1 until the sample breaks.
[0079] Battery discharge time: The zinc-air battery assembled with gel electrolyte, zinc sheet, and air cathode operates at a current density of 2 mA / cm². 2 Constant current discharge is performed under certain conditions.
[0080] Battery cycle stability time: The assembled zinc-air battery was tested at a current density of 2 mA / cm². 2 Under these conditions, a 5-minute charging and discharging process was performed respectively to complete the constant current charge-discharge cycle test of the battery.
[0081] Table 1. Comparison of key parameters between the examples and comparative examples.
[0082] Table 2. Elongation at break, electrical conductivity, water retention, and cycle time of the examples and comparative examples.
[0083] Note: The "\" in Table 2 indicates that the performance was not tested.
[0084] Figure 1 This is a comparison of the ionic conductivity of the gel electrolytes obtained in Examples 1-3 and Comparative Examples 1-4. It can be seen that Example 1 has the highest ionic conductivity, significantly higher than Examples 2 and 3, indicating that 0.3% is the optimal concentration; concentrations that are too high or too low are detrimental to ion transport. Under the same concentration (0.3%), the conductivity of Example 1 is significantly higher than that of Comparative Examples 1, 2, and 3, demonstrating that component one obtained through fractionation with 95% ethanol has the optimal molecular weight distribution and functional group activity, enabling the construction of more efficient ion transport channels in the PVA gel network. Comparative Example 4 (without lignin) has the lowest conductivity, proving the necessity of introducing alkali lignin to improve ionic conductivity.
[0085] Figure 2 This is a water retention curve of the gel electrolytes obtained in Example 1 and Comparative Examples 1-4 of the present invention after 48 hours in air at room temperature. Figure 2It can be seen that Example 1 has the highest water retention rate, which is attributed to its excellent water retention performance due to its abundant phenolic hydroxyl and carboxyl functional groups. These functional groups can effectively anchor water molecules through hydrogen bonding, forming a stable hydration layer and thus inhibiting water evaporation. Comparative Examples 1-4 show a decreasing water retention rate in that order, with Comparative Example 4 (without lignin) having the worst water retention rate, further verifying the unique advantages of graded alkali lignin (component 1) in water retention.
[0086] Figure 3 These are stress-strain curves of the gel electrolytes obtained in Examples 1-3 and Comparative Examples 1-4 of the present invention. Figure 3 It can be seen that Example 1 exhibits the highest tensile strength (1.1 MPa) and elongation at break (610%), demonstrating the best overall mechanical properties. Example 3 (0.5%) shows an even higher elongation at break (720%) but slightly lower tensile strength, while Example 2 (0.1%) has the second best mechanical properties. Compared to all comparative examples, Example 1 shows a significant improvement in both tensile strength and elongation at break, proving that graded alkali lignin and PVA form an effective hydrogen-bonded cross-linked network, with Example 1 achieving the best balance between tensile strength and elongation at break.
[0087] Figure 4 , Figure 5 The zinc-air batteries assembled in Example 1 and Comparative Examples 1-4 of this invention were used at a current density of 2 mA / cm². 2 The discharge curves and constant current charge-discharge curves were obtained. The results showed that Example 1 had the longest discharge time (34 h) and a cycle stability time of 124.35 h, both significantly better than Comparative Examples 1-4. This indicates that hierarchical lignin and the directional pore structure work synergistically. On the one hand, lignin anchors water molecules through functional groups and constructs efficient ion transport channels; on the other hand, the directional pores guide the rapid directional transport of ions. Together, they inhibit the growth of zinc dendrites and significantly improve the cycle stability and discharge performance of the battery.
[0088] The performance test results above demonstrate that this invention, through graded treatment with 95% ethanol to obtain graded alkali lignin with low molecular weight and abundant active functional groups, successfully prepared a zinc-air battery gel electrolyte with excellent comprehensive performance by introducing it into a polyvinyl alcohol-based hydrogel and combining it with anisotropic channels constructed by liquid nitrogen-assisted directional freezing of copper blocks. The introduction of graded lignin significantly improves ionic conductivity, water retention, and mechanical properties. Its abundant polar functional groups enhance the gel network and anchor water molecules through hydrogen bonding crosslinking, reducing the local concentration gradient of zinc ions. This, combined with the rapid ion transport pathway of the directional channels, effectively inhibits the growth and penetration of zinc dendrites. The raw materials of this invention are byproducts of the papermaking industry, making it environmentally friendly. The process is simple and mild, easy to scale up, and provides a new technical path for the development of high-performance zinc-air batteries.
[0089] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a zinc-air battery gel electrolyte based on hierarchical alkali lignin, characterized in that: Includes the following steps: Alkali lignin is mixed with an aqueous alcohol solution, stirred to dissolve, and the dissolved portion is collected. The solvent in the dissolved portion is removed to obtain graded alkali lignin, wherein the volume fraction of the aqueous alcohol solution is ≥80%. Graded alkali lignin is dissolved in an alkaline electrolyte solution to obtain an alkaline solution containing graded alkali lignin. The solutes in the alkaline electrolyte solution are potassium hydroxide and zinc acetate, with the concentration of potassium hydroxide being 4-7 mol / L and the concentration of zinc acetate being 0.1-0.5 mol / L. After degassing an aqueous solution of polyvinyl alcohol, it is subjected to directional freezing and thawing to obtain a PVA hydrogel with a directional pore structure. The PVA hydrogel was immersed in an alkaline solution containing graded alkali lignin to obtain a gel electrolyte. The alkaline solution containing graded alkali lignin has a mass-volume concentration of 0.1% to 0.5%, w / v. The method of directional freezing and thawing is as follows: pour the polyvinyl alcohol solution into the mold, and apply the metal block in contact with liquid nitrogen to one side of the polyvinyl alcohol solution for rapid directional freezing; After complete freezing, transfer the mold to an environment of -25~-15℃ and continue freezing for 10-15 hours; Then thaw at 20-30℃.
2. The method for preparing zinc-air battery gel electrolyte based on hierarchical alkali lignin according to claim 1, characterized in that: The alcohol in the aqueous solution is methanol, ethanol, or propanol; Alternatively, the volume fraction of the aqueous alcohol solution is ≥90%.
3. The method for preparing zinc-air battery gel electrolyte based on hierarchical alkali lignin according to claim 1, characterized in that: The solvent in the dissolved portion is removed by rotary evaporation concentration to remove ethanol, followed by freeze drying to fractionate alkali lignin.
4. The method for preparing zinc-air battery gel electrolyte based on hierarchical alkali lignin according to claim 1, characterized in that: The solutes in the alkaline electrolyte solution are potassium hydroxide and zinc acetate, with the concentration of potassium hydroxide being 4-6 mol / L and the concentration of zinc acetate being 0.1-0.3 mol / L.
5. The method for preparing zinc-air battery gel electrolyte based on hierarchical alkali lignin according to claim 1, characterized in that: The concentration of polyvinyl alcohol in the aqueous solution is 5-15%, w / v.
6. The method for preparing zinc-air battery gel electrolyte based on hierarchical alkali lignin according to claim 1, characterized in that: The directional freezing and thawing operation is repeated 2-4 times; during each directional freezing, the metal block acts on the same side of the polyvinyl alcohol.
7. The method for preparing zinc-air battery gel electrolyte based on hierarchical alkali lignin according to claim 1, characterized in that: The PVA hydrogel was soaked in the alkaline solution containing graded alkali lignin for 10-15 hours at a temperature of 20-30°C.
8. A zinc-air battery gel electrolyte based on graded alkali lignin, characterized in that: It is prepared by any of the preparation methods described in claims 1-7.
Citation Information
Patent Citations
Nanocellulose composite PVA (polyvinyl alcohol) material and preparation method and application thereof
CN106835345A
PVA / EGCG / Ag acidic gel electrolyte, preparation method thereof and novel zinc-air battery
CN118507932A